Thermally induced planar defect formation in sputtered V1-xMoxB2-Δ films. (May 2023) - Viskupová, Katarína; Grančič, Branislav; Roch, Tomáš; Nagy, Štefan; Satrapinskyy, Leonid; Šroba, Viktor; Truchlý, Martin; Šilha, Jiří; Kúš, Peter; Mikula, Marián
Abstract: This work reports on various thermally induced planar defects formed in ternary V1-x Mox B2-Δ coatings with different influence on mechanical properties. V0.58 Mo0.42 B1.9 and V0.37 Mo0.63 B1.2 films were prepared by magnetron sputtering and annealed in vacuum up to 1300 °C. Depending on the stoichiometry, different types of planar defects were identified by scanning transmission electron microscopy (STEM). In the slightly understoichiometric V0.58 Mo0.42 B1.9 system, anti-phase boundary defects (APB) were observed, which was accompanied by chemical separation of V and Mo. Accumulation of these defects led to formation of MoB-Cmcm orthorhombic phase in otherwise hexagonal VB2 -P6/mmm structure, with no apparent effect on mechanical properties. On the other hand, in case of the highly understoichiometric V0.37 Mo0.63 B1.2 coating, no chemical separation was observed. Here, annealing resulted in crystallization from amorphous state into orthorhombic Cmcm phase with high density of twin lamellae, which was accompanied by a significant hardening. Graphical abstract: Image, graphical abstract